Theorizing Community for Sport Management Research and Practice - Rich, Kyle A.; Spaaij, Ramón; Misener, Laura (Frontiers in Sports and Active Living, 2021)
Community is a context for much research in sport, sport management, and sport policy, yet relatively few authors explicitly articulate the theoretical frameworks with which they interrogate the concept. In this paper, we draw from communitarian theory and politics in order to contribute to a robust discussion and conceptualization of community in and for sport management research and practice. We provide a synthesis of current sport management and related research in order to highlight contemporary theoretical and methodological approaches to studying community. We distinguish between community as a context, as an outcome, as a site for struggle or resistance, as well as a form of regulation or social control. We then advance a critical communitarian agenda and consider the practical implications and considerations for research and practice. This paper synthesizes current research and establishes a foundation upon which sport management scholars and practitioners might critically reflect on community and deliberatively articulate its implications in both future research and practice.